Assessment of creep behavior using a damage-coupled model for martensitic stainless steel - Sungmin YOON (The Japan Society of Mechanical Engineers, 2021)
In this study, the Liu–Murakami (LM) creep damage-coupled model was considered to evaluate the creep properties of martensitic stainless steel. The degree of creep damage was examined at two temperatures (565 ℃ and 593 ℃) to assess mechanically and thermally activated processes. A series of high applied stresses (applied stress/ultimate strength > 0.5) was considered for accelerated creep loadings. A full set of creep constants was determined by combining the Norton and LM models. Constitutive equations were used to quantitatively estimate experimental creep curves. The variation in creep constants was discussed based on stress sensitivity, such as stress triaxiality and applied stress, depending on the power of stress. The creep strain–time curves were successfully estimated. The comparison between the experimental and analytical results was in good agreement in the tertiary regime. In addition, the compensation of the two applied temperatures provides a supplementary explanation of the relationship between the ultimate strength and rupture time in terms of temperature sensitivity. The analytical results show that different applied stresses and temperatures could be compensated to characterize the creep behavior of the material. Thus, the creep strain–time and creep strain rate–certain rupture time curves were finally achieved. The analytical process in this study provides a laboratory-scale assessment of creep properties using the accelerated creep test and LM model.